Steroid-induced cataract and glaucoma in pediatric patients with nephrotic syndrome - Lee Ryan N. Olonan, MD; Catherine Anne G. Pangilinan, MD; Mario M. Yatco, MD (Philippine Journal of Ophthalmology)
Objective: This study investigated ocular complications, such as cataract and glaucoma, arising from prolonged corticosteroid therapy in children.